S&T Priorities for Modernization of Russian Economy - Sergey Shashnov; Anna Poznyak (Foresight and STI Governance, 2011)
The paper discusses the results of revising the lists of S&T priorities and critical technologies of the Russian Federation, adopted in 2006 that became the basis for the federal targeted R&D program for the period of 2007-2012. The identification of priorities aims at more efficient budget planning. The lists of S&T priorities and critical technologies are adjusted and updated every four years. The updated lists allow mobilizing available resources on those areas which are associated with the largest economic and social effects as well as improving science, technology and innovation policies. In addition owing to the adjustment of priorities and developing roadmaps businesses get a clear view on the possibilities of commercialization and development of breakthrough solutions related to critical technologies while investors reveal promising directions and best conditions of investment. The authors present in detail the stages of adjusting and selecting the priorities by analyzing the established practices and trends in Russia, European countries as well as on the international level. According to the results of this work six core priority areas have been identified. Compared to the 2006 edition the renewed list was reduced significantly, from 34 to 25 positions. The number of critical technologies decreased in all directions, except for «Transport and Space Technology». Five technologies retained their wording unchanged, in 11 cases the formulations have been adjusted while the rest changed significantly. The list of critical technologies reflects the latest scientific and technological trends in conjunction with the objectives of socio-economic development. In the short term one may expect scientific and technological breakthroughs in these areas that will lead to the emergence of new markets, increasing competitiveness of domestic products, a higher quality of life and national security. They are all characterized by significant economic, social and environmental effects.